2016
DOI: 10.5539/ijps.v8n3p50
|View full text |Cite
|
Sign up to set email alerts
|

Diversity from within: The Impact of Cultural Variables on Emotion Expressivity in Singapore

Abstract: Culture is intrinsically linked with emotion expression, as culture provides rules regarding how to manage emotions when they occur. Thus far, existing literature has extensively compared norms for emotional expression and suppression, revealing significant differences among culturally distinct but also geographically distant groups (e.g., "collectivistic" Chinese versus "individualistic" U.S. Americans). The present study examines the impact of cultural diversity within Singapore, a heterogeneous Asian nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Finally, mothers in the present study exhibited minimal warmth in the form of hugs, kisses, praises and smiling. This concurs with previous findings showing that Singaporean parents tend to not be emotionally expressive (Quah, 1999), and in line with the perceived value of exercising emotional restraint in the Singaporean context (Hurley et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, mothers in the present study exhibited minimal warmth in the form of hugs, kisses, praises and smiling. This concurs with previous findings showing that Singaporean parents tend to not be emotionally expressive (Quah, 1999), and in line with the perceived value of exercising emotional restraint in the Singaporean context (Hurley et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In one of the first observation studies on maternal sensitivity in Singapore, a city state in Southeast Asia with a majority ethnic Chinese population, Cheung and Elliott (2016) found that preschoolers whose mothers were sensitive tended to be less well-liked by female peers, which is inconsistent with evidence showing that enhanced parental sensitivity predicts children's positive social development (Deans, 2020). Cheung and Elliott (2016) contended that the use of the Emotional Availability (EA) Scales (Biringen, 2008) in that study, with its focus on positive affective communication in the assessment of sensitivity, may have been less appropriate in the Singaporean context where emotional restraint, self-control and emotion suppression are common regulation strategies (Hurley et al, 2016). To illustrate, the EA sensitivity scale posits that an integral part of caregiver sensitivity involves "appropriate and positive affective exchanges… [with] clear and accurate perceptions of emotions, as well as responsiveness" (Biringen & Easterbrooks, 2012, p. 3).…”
Section: Ainsworth and Emotional Availability Scalesmentioning
confidence: 78%
“…This finding is in line with findings of previous studies, where Japanese typically tend to avoid negative outcomes and thus engage in fewer negative emotions [37,38]. Evidence suggests that generally Asians suppress their negative emotions when perceiving out-group emotions, but not positive emotions such as happiness [39]. In this study, it was noted that all Asian groups perceived happiness higher than the Spanish listeners.…”
supporting
confidence: 92%
“…Similar to the study by Li et al (2010) which reported a positive association between authoritarian parenting and socioemotional adjustment in China, Chong and Chan (2015) found that Singaporean adolescents with authoritarian mothers tended to have better self-management of emotions. This is likely because the highly controlling nature of authoritarian parenting serves to inhibit emotional expressions among adolescents, where emotional restraint is a valued characteristic that is practised and encouraged in the Singaporean context (Hurley et al, 2016).…”
Section: Authoritarian Stylementioning
confidence: 99%
“…Furthermore, few studies have looked at the concept of parental warmth in Singapore, where emotional restraint and suppression is practised and encouraged (Hurley et al, 2016). It remains to be known whether the concept of warmth needs to be further expanded to include examples of instrumental aid beyond overt physical and emotional expressions of love (e.g., Cheah et al, 2015).…”
Section: Recommendations For Research and Practicementioning
confidence: 99%